Special Issue: Pathogenic Escherichia coli: Infections and Therapies - Margarita Martinez-Medina (MDPI AG, 2021)
Escherichia coli is a facultative anaerobic Gram-negative bacterium from the Enterobacteriaceae family that colonizes the gastrointestinal tract of warm-blooded animals shortly after birth, and it is a lifelong colonizer of adults [...]